Posttraumatic pneumopericardium: a sign of severe injury or radiodiagnostic rarity? - Lonský, Vladimír; Mand'ák, Jirí; Harrer, Jan; Tuna, Martin; Dvorák, Petr; Dedek, Tomás; Dominik, Jan (Acta medica (Hradec Kralove), 2006)
We present three cases of pneumopericardium following blunt chest trauma injury. All three patients were victims of road traffic accidents. All had multiple associated injuries and pneumopericardium was found as the additional finding. Pneumopericardium was treated conservatively with thoracic drains placement and patients observation. Transesophageal echocardiography was used as a method of choice for exclusion of cardiac air tamponade. All three patients survived.
Keywords: Thoracic Injuries; pneumoperikard; Accidents, Traffic; mužské pohlaví; radiografie; dospělí; Humans; Radiography; Adult; Wounds, Nonpenetrating; dopravní nehody; Pneumopericardium; Adolescent; poranění hrudníku; tupá poranění; lidé; Male; mladiství